Exploring the Knowledge Filter - How Entrepreneurship and University-Industry Relations Drive Economic Growth - Pamela Mueller (European Regional Science Association (ERSA), 2005)
Why do regions post different growth rates and differences in technological progress? Knowledge creation and knowledge spillovers are an important element in stimulating economic development. Recent empirical studies have shown that knowledge spillovers positively affect technological change and economic growth. Other studies have shown that knowledge spillovers do not occur automatically, hence, it is less clear which mechanisms facilitate and foster knowledge flows. This paper focuses on the exploitation of opportunities and commercialization of knowledge, namely the transformation of knowledge into products, processes and organizations, and their contribution to regional economic growth. The degree of knowledge exploitation may differ across regions because the level of research and development activities varies, incumbent firms might not exploit new opportunities to the full extent, and new knowledge generated in research institutions and universities is hardly translated into new products or services . It may be argued that a knowledge filter exists limiting the total conversion of knowledge into new products, processes and organizations (for details, see Acs, Audretsch, Braunerhjelm & Carlsson, 2003). This paper introduces entrepreneurship and university-industry relations as mechanisms for knowledge spillovers and determinants of economic growth. Entrepreneurial activity can be assumed as a mechanism by which knowledge spillover occurs. Many radical innovations have been introduced by new firms rather than by incumbents, because the set-up of one's own business might be the most promising possibility to commercialize knowledge (Audretsch, 1995). University-industry relations may be another mechanism facilitating the exploitation of knowledge and the flow of ideas (Mansfield, 1991, 1998). If the generated knowledge at universities is transferred via research partnerships it may accelerate technology transfer and enable firms to develop new products and process (Cohen, Nelsen & Walsh, 2002, Mansfield 1991 and 1998). The empirical modeling framework develops a regional model of economic growth and analyzes if the region's absorptive capacity, entrepreneurship and university-industry relations drive economic growth. The results of the empirical analysis suggest that new ventures and partnerships between university and industry amplify the permeability of the knowledge filter and thus spur economic growth. The paper also gives an outlook and discusses implications for public policy to stimulate entrepreneurship and university-industry relations.
Keywords: 330